THE THE REALIZATION OF LEECH’S MAXIMS IN THE STUDENTS’ INTERACTIONS - Mella lidyana Sari (JAMBI-ENGLISH LANGUAGE TEACHING, 2021)
ABSTRACT  Sari, Mella Lidyana. 2021. The Realization of Leech’s Maxims in the Students’ Interactions. A Graduating Paper of English Department. Faculty of Teacher Training and Education, The University of Jambi in Academic Year 2020/2021. The first supervisor is Dr. Dra. Rachmawati, M. Pd. The second supervisor is Tubagus Zam Zam Al Arif, S. Pd., M. Pd.     This research aimed to identify the types of politeness maxims realized by the students in the classroom interactions. This research used a qualitative method. The subject of this research was the students from regular 001 2017 in the 5th semester in the English Department at the University of Jambi. There are 28 students as the participants of this study that consists of 27 females and 1 male. There is a research instrument in collecting the data, namely audio recording. Besides, there are some steps of analyzing the data that were data reduction, transcribing, identification, classification, and data display. The findings of this research were five politeness maxims realized by the students, namely: tact maxim, generosity maxim, approbation maxim, agreement maxim, and sympathy maxim. On the other hand, the students have realized the five politeness maxim proposed by Leech. Besides, the most maxim realized by the students is the tact maxim and the modesty maxim is the only maxim that did not realize by the students in interactions. So, the students have realized the maxims 20 times in 2 courses for 4 meetings.     Keywords: Politeness Principles, Students’ Interactions.